Naturalization, reciprocity and marks of marital violence: male defendants' perceptions - Gilvânia Patrícia do Nascimento Paixão; Alvaro Pereira; Nadirlene Pereira Gomes; Anderson Reis de Sousa; Fernanda Matheus Estrela; Ubirajara Ramos Pereira da Silva Filho; Igor Brasil de Araújo
ABSTRACT Objective: to analyze male criminals' perception about marital violence. Method: An exploratory, descriptive, qualitative study undertaken with 23 men who were criminally prosecuted for marital violence. A multimethod data collection was conducted, with individual interview and focal group techniques combined, between May and December 2015. The data collected were initially categorized using the NVIVO® 11 software program, and then organized using the Collective Subject Discourse method. Results: the collective discourses reveal that, in the male's perception, conjugal violence is inherent in a marital relationships: it is a private, reciprocal problem that leaves body marks. Conclusion: gender dissymmetry as a social construct is evidenced, signaling the need to create spaces for reflection and re-signification of men and women, from a gender perspective.